Correction: Locality and diel cycling of viral production revealed by a 24 h time course cross-omics analysis in a coastal region of Japan. Issue 12 (December 2018) - Yoshida, Takashi; Nishimura, Yosuke; Watai, Hiroyasu; Haruki, Nana; Morimoto, Daichi; Kaneko, Hiroto; Honda, Takashi; Yamamoto, Keigo; Hingamp, Pascal; Sako, Yoshihiko; Goto, Susumu; Ogata, Hiroyuki
The original version of this Article contained an error in the main text citations and reference list. These errors have now been corrected in both the PDF and HTML versions of the Article.